The Role of Dectin-1 Signaling in Altering Tumor Immune Microenvironment in the Context of Aging - Bhaskaran, Natarajan; Jayaraman, Sangeetha; Quigley, Cheriese; Mamileti, Prerna; Ghannoum, Mahmoud; Weinberg, Aaron; Thuener, Jason; Pan, Quintin; Pandiyan, Pushpa (Frontiers in Oncology, 2021)
Abstract An increased accumulation of immune-dysfunction-associated CD4+Foxp3+ regulatory T cells (Tregs) is observed in aging oral mucosa during infection. Here we studied the function of Tregs during oral cancer development in aging mucosa. First, we found heightened proportions of Tregs and Myeloid-derived suppressor cells (MDSC) accumulating in mouse and human oral squamous cell carcinoma (OSCC) tissues. Using mouse 4-Nitroquinoline 1-oxide(4-NQO) oral carcinogenesis model, we found aged mice displayed increased propensity to epithelial cell dysplasia, hyperplasia, and accelerated OSCC development, which coincided with a significantly increased abundance of IL-1, Tregs, and MDSC in tongues. Partial depletion of Tregs reduced tumor burden. Moreover, fungal abundance and Dectin-1 signaling were elevated in aged mice suggesting a potential role for Dectin-1 in modulating immune environment and tumor development. Corroborating to this tenet, Dectin-1 deficient mice showed diminished IL-1, reduced infiltration of Tregs and MDSC in the tongue, as well as slower progression and reduced severity in tumor burden, revealing that Dectin-1 signaling plays a critical role in promoting tumor incidence and cancer progression. Taken together, these data identify an important role of enhanced Dectin-1 signaling in establishing the intra-tumoral immunosuppressive milieu and promoting OSCC tumorigenesis in the context of aging.